Geochemistry and Potential Hydrocarbon Source Rocks of Rambatan Formation in Karangkobar Area, Central Java - Praptisih Praptisih; Yoga Andriana Sendjaja; Vijaya Isnaniawardhani; Anggoro Tri Mursito; Purna Sulastya Putra; Septriono Hari Nugroho (Universitas Gadjah Mada, 2022)
The purpose of the study in the Karangkobar area was to investigate the source rock potential of the fine-grained surface samples of clastic sediments. The use of surface samples for source rock potential study in Indonesia is still limited. We conducted geochemical laboratory analyses in this research, including Total Organic Carbon (TOC), Rock-Eval Pyrolysis (REP), and Gas chromatography–mass spectrometry (GCMS). Seventeen samples have been analyzed for their TOC content. The result shows that TOC values varied between 0.36–1.55%, indicating that the source rock potential level based on the surface samples is poor to fair organic richness. REP was conducted on 16 samples, and the results show that the hydrocarbon-generating characteristics (HI values) ranged from 15 to 163 mg HC/g TOC. The kerogens identified included type II and III kerogen, which indicated the oil and gas-generating potential. Pyrolysis temperature is at maximum (Tmax) in the 276–458 °C, indicating that the samples were thermally immature to mature. GCMS analysis of source rock indicated that the depositional environment of the organic material derived from an open marine and plankton environment. This study is essential to complete the understanding of the petroleum system in Central Java.